Digital and smart cities - Willis, Katharine S. (Routledge critical introductions to urbanism and the city, 2018)
Digital and Smart Cities presents an overview of how technologies shape our cities. There is a growing awareness in the fields of design and architecture of the need to address the way that technology affects the urban condition. This book aims to give an informative and definitive overview of the topic of digital and smart cities. It explores the topic from a range of different perspectives, both theoretical and historical, and through a range of case studies of digital cities around the world.